This research has been held since February to November 2008 in the Research Laboratory and Teaching Farm of KPBI (Koperasi Peternak Babi Indonesia), Cisarua District, Bandung Regency and Nutrition Laboratory, Animal Husbandry Faculty, Padjadjaran University. The purpose of this research is to know the effective dosage of curcumin to give equivalent influence with virginiamycin as growth promotor in pig. This research use completely randomized design consisting of five treatments (Rvm: 50 ppm vi - Sauland Sinaga; D.T.H. Sihombing; Maria Bintang; Kartiarso . (Forum Pasca Sarjana, 2010)
This research has been held since February to November 2008 in the Research Laboratory and Teaching Farm of KPBI (Koperasi Peternak Babi Indonesia), Cisarua District, Bandung Regency and Nutrition Laboratory, Animal Husbandry Faculty, Padjadjaran University. The purpose of this research is to know the effective dosage of curcumin to give equivalent influence with virginiamycin as growth promotor in pig. This research use completely randomized design consisting of five treatments (Rvm: 50 ppm virginiamicin, R0: tanpa virginiamicin dan curcumin, R1: 120 ppm curcumin, R2: 160 ppm curcumin, and R3: 200 ppm curcumin), with five treatment. This research used 25 starter period pigs, age 2 months with weight rate of 18 kg and variation coefficient of 6.33%. The result shows that giving curcuminoid as feed additive 160 ppm in pig ration significant by influenced to digestible energy, the rate of passage of feed, body weight gain, feed efficiency and time to slaugter weight. It is concluded that curcumin with dose of 160 ppm in pig ration will be able to replace virginiamycin as growth promotor. Key words: curcumin, virginiamicin, pig